Answer:
The function
and
are inverse function.
Step-by-step explanation:
Function inverse definition:
If a provided function <em>f(x)</em> is mapped <em>x</em> to <em>y</em>, then the inverse of the provided function <em>f(x) </em>is mapped <em>y</em> to <em>x</em>.
Or ![f(x)=f(y)\Rightarrow x=y](https://tex.z-dn.net/?f=f%28x%29%3Df%28y%29%5CRightarrow%20x%3Dy)
Now, consider the function <em>y</em> =<em> x</em>.
Interchange the variables <em>x</em> and <em>y</em>.
![x=y](https://tex.z-dn.net/?f=x%3Dy)
Now, solve
for
.
![x=y](https://tex.z-dn.net/?f=x%3Dy)
Therefore, this function has an inverse.
Consider the function
.
Interchange the variables <em>x</em> and <em>y</em>.
![x=y^{2}](https://tex.z-dn.net/?f=x%3Dy%5E%7B2%7D)
Now, solve
for
.
![\pm \sqrt{x} =y](https://tex.z-dn.net/?f=%5Cpm%20%5Csqrt%7Bx%7D%20%3Dy)
Therefore, the function has no inverse.
Consider the function
.
Interchange the variables <em>x</em> and <em>y</em>.
![x=y^{3}](https://tex.z-dn.net/?f=x%3Dy%5E%7B3%7D)
Now, solve
for
.
![\sqrt[3]{x}=y](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%7D%3Dy)
Therefore, the function has inverse.
Consider the function
.
Interchange the variables <em>x</em> and <em>y</em>.
![x=y^{4}](https://tex.z-dn.net/?f=x%3Dy%5E%7B4%7D)
Now, solve
for
.
![\pm \sqrt[4]{x}=y](https://tex.z-dn.net/?f=%5Cpm%20%5Csqrt%5B4%5D%7Bx%7D%3Dy)
Therefore, the function has no inverse.
Hence, the function
and
are inverse function.